2017
DOI: 10.1007/s12020-017-1281-x
|View full text |Cite
|
Sign up to set email alerts
|

MKRN3 levels in girls with central precocious puberty and correlation with sexual hormone levels: a pilot study

Abstract: We showed that girls with central precocious puberty had lower peripheral levels of MKRN3 compared to age-matched pairs and that they negatively correlated to gonadotropins, estrogen, and BMI. Our findings support the MKRN3 involvement in central precocious puberty also in absence of deleterious mutations, although our sample size is small. In addition our data suggest the role of MKRN3 in the complex mechanism controlling puberty onset and its interaction with other factors affecting puberty such as nutrition. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 29 publications
7
25
2
2
Order By: Relevance
“…Similarly, in the present study, MKRN3 levels declined after the initiation of GnRH in the whole population, and the MKRN3 serum level modifications were evident, independently from the absolute serum levels detected. Moreover, in our previous work, we found that levels of MKRN3 in CPP girls were similar to those found in the present report [22], making MKRN3 assay results in our laboratory consistent.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similarly, in the present study, MKRN3 levels declined after the initiation of GnRH in the whole population, and the MKRN3 serum level modifications were evident, independently from the absolute serum levels detected. Moreover, in our previous work, we found that levels of MKRN3 in CPP girls were similar to those found in the present report [22], making MKRN3 assay results in our laboratory consistent.…”
Section: Discussionsupporting
confidence: 91%
“…Despite these differences, the serum levels of MKRN3 showed the same trend: levels declined before puberty onset and were lower in patients with precocious puberty compared with matched healthy subjects [19-22]. Similarly, in the present study, MKRN3 levels declined after the initiation of GnRH in the whole population, and the MKRN3 serum level modifications were evident, independently from the absolute serum levels detected.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations